Twitter and Stakeholder Engagement in the Rio 2016 Paralympics - Gassewitz, Debra (Université d'Ottawa / University of Ottawa, 2020)
The purpose of this study is to use the stakeholder salience model and social network analysis, with a particular focus on the concept of urgency and strength of weak ties, to identify and explore new and previously unknown stakeholders for the Canadian Paralympic Committee using Twitter conversations during the Rio 2016 Paralympic Games. Given the Paralympic Games are hosted globally, and digital and social media are increasingly used as the source for content delivery, sport organizations need to understand who their social media stakeholders are and how to maximize the audience experience. Findings supported the importance of urgency within the context of Twitter and the need to consider both strong and weak ties with the significant appearance of individuals as previously unidentified stakeholders and the emergence of both Paralympic and Olympic athletes as influencers. This research contributes to baseline data about Paralympic sport stakeholders and stakeholder engagement on social media.
Keywords: Stakeholder identification; Twitter; Social Network Analysis; Paralympics